Co-morbidity and Age-related Prevalence of Psoriasis: Analysis of Health Insurance Data in Germany - Augustin, M; Reich, K; Glaeske, G; Schaefer, I; Radtke, M (Acta dermato-venereologica, 2010)
Epidemiological studies indicate an increased risk of co-morbidities and an association with other inflammatory diseases in psoriasis. However, most analyses have been performed on small samples of patients. The aim of this study was to evaluate the prevalence of co-morbidities in psoriasis based on a large set of health insurance data. The database of 1.3 million patients in a German nationwide statutory health insurance scheme was analysed. Data-sets of patients with confirmed psoriasis were extracted and analysed for co-morbidities. Of 1,344,071 subjects, 33,981 had a diagnosis of psoriasis (prevalence 2.5%). Metabolic syndrome was 2.9-fold more frequent among these patients. The most common diagnoses were arterial hypertension (35.6% in psoriasis vs. 20.6% in controls) and hyperlipidaemia (29.9% vs. 17.1%). The frequencies of rheumatoid arthritis (prevalence ratio (PR) 3.8), Crohn's disease (PR 2.1) and ulcerative colitis (PR 2.0) were also increased among patients with psoriasis. In conclusion, psoriasis is associated with significant co-morbidities that imply an elevated risk of severe complications.